The influence of fire-grazer interactions on forb communities in a highveld grassland - Parrish, Margaret Doris (Percy FitzPatrick Institute of African Ornithology, 2018)
In southern Africa, disturbance contributes to the heterogeneity of grassland and savanna ecosystems. Fire and grazing act as the primary disturbances in these systems, and interactions between the two are common. As such, an understanding of the relationship between fire and grazing is essential for the conservation of biotic diversity and the production of high-quality forage for game and livestock. Frequent fires followed by concentrated grazing have been shown to facilitate patches of short, palatable grasses ("grazing lawns") within grassland and savanna landscapes. The effects of grazing lawn management on other aspects of biodiversity have received little attention. Forbs (non-graminoid, herbaceous plants) are an important component of grassland ecosystems, but how they respond to disturbance is largely unknown. This study compared changes in forb communities on and off of firebreaks (an extreme example of a grazing lawn) in a high altitude mesic grassland. Native herbivore biomass was significantly higher on firebreaks than in the surrounding lightly grazed matrix and the firebreaks, while more compacted, did not show significant signs of degradation. There were no significant differences in forb abundance or richness between annually burned and intermittently burned plots, and there was no species turnover associated with the annually burned, heavily grazed treatment. Speciesspecific differences in functional traits on annually burned and intermittently burned plots were likely a function of light limitation, as mammalian palatability scores were nominal. Ultimately, ten years of intensive fire and grazing have had minimal impact on forb communities in a high altitude mesic grassland. The results indicate that in this type of Highveld grassland, heavily grazed and annually burned patches are not detrimental to the forb community and clearly enhance habitat diversity for grazers.